Quelques mots sur la recevabilité des éléments de preuve extrinsèques devant les tribunaux : le Canada et les États-Unis - Hudon, Edward (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
This article is a comparison of the use of extrinsic materials by the courts of Canada and of the United States in the interpretation of statutes. The author points out that in the United States the courts have reached the point where just about everything is admissible — particularly legislative debates, committee hearings and reports — but that in Canada the use of extrinsic materials is limited to the determination of the constitutionality of a law or statute. Although the courts of Canada are becoming more and more liberal in the use of extrinsic materials, the use of legislative debates is still not generally permitted even though they were used by one Justice of the Supreme Court of Canada in the Anti-Inflation Act Reference. The author wonders how long it will be before the Supreme Court of Canada will abandon the little that is left of the English tradition and permit the use of extrinsic materials not only in the determination of the constitutionality of a statute, but also in its interpretation.